2019
DOI: 10.1097/gox.0000000000002213
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix Reduces Myofibroblast Presence in the Breast Capsule

Abstract: Background: Capsular contracture remains a common complication after implant-based breast reconstruction. Previous work has suggested that the use of acellular dermal matrix (ADM) reduces the rate of capsular contracture, though little is understood about the underlying mechanism. As myofibroblasts are believed to be the key cells implicated in contracture formation, we hypothesized that ADM would result in a reduction in periprosthetic myofibroblast concentration. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 26 publications
1
36
0
1
Order By: Relevance
“…Although the histological examination was performed in a single case, the result showed more decreased number of myofibroblasts in the CGCRYODEROM capsule. It is reported that decreased presence of myofibroblasts is related to reduced capsular contracture rates with addition of ADM in IBR (27,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Although the histological examination was performed in a single case, the result showed more decreased number of myofibroblasts in the CGCRYODEROM capsule. It is reported that decreased presence of myofibroblasts is related to reduced capsular contracture rates with addition of ADM in IBR (27,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…24 Limited other data exist directly comparing the specific inflammatory response in the breast implant capsule based on adjacent tissue type. However, capsule adjacent to ADM compared with capsule against muscle in the same breast shows significantly reduced inflammation and cellularity in capsule against ADM. [25][26][27][28] This, coupled with the fact that ADM appears to reduce capsular contracture, raises the possibility that adjacent tissues drive periprosthetic inflammation, and that ADM shields the implant from this inflammatory response. 8,9 Another plane-specific consideration is that breast parenchyma also possesses low levels of bacterial colonization.…”
Section: Cellular and Molecular Origin Of Capsular Contracturementioning
confidence: 99%
“…In such a scenario, even if autologous procedures remain excellent reconstructive strategies, their very long operating times, the need for donor site availability, and the associated possible complications explain why many surgeons opt for the simpler and faster implant-based reconstruction (IBR), currently the most common approach ( 4 , 9 , 10 ). In this regard, although improvements in silicone implant safety and fat grafting techniques have been contributing to the growth of prosthetic reconstruction ( 6 , 11 ), the historical development of IBR has been accompanied first by the introduction and then by the evolution of several generations of collagen-based materials such as acellular dermal matrices (ADMs) ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%